A rare case of pseudomyogenic hemangioendothelioma (PHE)/epithelioid sarcoma-like hemangioendothelioma (ES-H) of the breast first misdiagnosed as metaplastic carcinoma by FNAB and review of the literature - Yan Ge; Xingtao Lin; Fen Zhang; Fangping Xu; Luqiao Luo; Weiye Huang; Zhihua Liu; Yanhui Liu; Zhi Li (BMC, 2019)
Abstract Aims Pseudomyogenic hemangioendothelioma (PHE)/epithelioid sarcoma-like hemangioendothelioma (ES-H) is a rare vascular tumor of intermediate malignancy that commonly occurs in soft tissue of distal extremities of young adults. PHE typically has a multifocal presentation and can involve several tissue planes, including the dermis, subcutis, muscle and bone. Methods and results We present here a unique case of PHE/ESH that arose in the breast as well as a review of the published literature. The initial biopsy was interpreted as a metaplastic carcinoma. However, complete resection largely revealed plump epithelioid cells, and a more spindled cell component was also noted. The cells displayed abundant eosinophilic cytoplasm and central vesicular nuclei arranged in loose fascicles, with a mild, mixed acute and chronic inflammatory infiltrate. Overall, linear membranous staining of CD31 and lack of CD34 expression were highly suggestive of PHE. At the same time, FOSB immunoreactivity was observed, which supported PHE/ESH instead of metaplastic carcinoma. The patient has not shown recurrence in the half year follow up after total mastectomy. Conclusion To our knowledge, this is the first report of breast involvement in this neoplasm. Recognition of its histopathological features and immunohistochemical reactivity will prevent misdiagnosis of breast lesions.